Trends in body mass index, blood pressure and parental smoking habits in middle socio-economic level Turkish adolescents - ÖZGÜVEN, SALİH (NATURE PUBLISHING GROUP, 2008)
Patterns of cardiovascular risk factors in populations are not static over time. We examined trends in body mass index (BMI), parental smoking and blood pressure over a 15-year period in Turkish children aged 15-17 years. Two cross-sectional studies were performed in secondary schools in Turkey in 1989-1990 and 2004-2005. Study participants were 673 children in 1989-1990 and 640 adolescents in 2004-2005. Main outcome measures were weight, height, BMI, presence and amount of parental smoking, systolic and diastolic blood pressure. Age and sex matched comparisons were performed to assess temporal trends in these measures. Children in 2004-2005 had increased weight, height, BMI and decreased systolic and diastolic blood pressure in all age groups compared with children in 1989-1990. According to the international criteria, 3.4% of children were obese and 15.8% were overweight in 2005, compared to 0.7% obese and 4.2% overweight in 1990 (P<0.001). However, a decrease was noted in blood pressure; 16% were classified as hypertensive in 1989-1990 versus 8% in 2004-2005 (P<0.001). The prevalence and amount of parental smoking also decreased over the last 15 years. We observed significant changes in BMI and blood pressure in Turkish children over the last 15 years. Temporal trends in these parameters may indicate a change in the pattern of cardiovascular disease in this population.
Keywords: cardiovascular risk factors; trends; blood pressure; body mass index; parental smoking; adolescents; METABOLIC SYNDROME; BIRTH-WEIGHT; RISK-FACTORS; INSULIN-RESISTANCE; SECULAR TRENDS; HEART-DISEASE; CHILDREN; CHILDHOOD; BOGALUSA; OBESITY